Analysis of Forest Vegetation in the Permanent Preservation Plot of Tamna in Orissa - Verma, R. K.; Totey, N. G.; Gupta, B. N. (Indian Forester, 1997)
Shorea robusta is dominant in preserved and unpreserved areas having maximum IVI, density, frequency and abundance. The higher value of diversity index in preserved plot than unpreserved one indicates more stable community in the preserved plot. The distribution of tree species in this forest is characterised by random and regular distribution. The population structure of tree species is represented mainly by two patterns. One pattern is represented by greater proportion of individuals in seedling stage indicating frequent reproduction. Another pattern indicates individuals in intermediate girth classes, wherein disturbances prevent regeneration thereby absence of seedlings. If such a trend continues for longer period, these species may disappear from this area in near future.